Printing-friendly sequential deposition via intra-additive approach for roll-to-roll process of perovskite solar cells. (November 2017) - Heo, Youn-Jung; Kim, Jueng-Eun; Weerasinghe, Hasitha; Angmo, Dechan; Qin, Tianshi; Sears, Kallista; Hwang, Kyeongil; Jung, Yen-Sook; Subbiah, Jegadesan; Jones, David J.; Gao, Mei; Kim, Dong-Yu; et al.
Abstract: We report organic cation additives in lead iodide solutions as a practical approach for roll-to-roll production of perovskite solar cells. Sequential deposition, which is known to be more reliable than 1 step process, is modified to be even more reliable and suitable in roll-to-roll process. Addition of less than stoichiometric amount of organic cations in PbI2 solution effectively improves processability by working as crystallization retardant and make dried PbI2 film more reactive for faster conversion to perovskite. The printing-friendly sequential deposition is used in air with slot die coating, an industrial up-scaling technique, to produce a perovskite solar cell on glass with a 14.4% power conversion efficiency (PCE). The process is then used in actual roll-to-roll machine in air to produce flexible perovskite solar cells with up to 11.0% PCE. Graphical abstract: Highlights: Conventional sequential deposition is modified to be more suitable for roll-to-roll process. Reactive intermediate shows more rapid conversion to perovskite than conventional PbI2 intermediate. Fully slot die coated perovskite solar cells under ambient condition shows a power conversion efficiency of 14.4%. Roll-to-roll processed flexible perovskite solar cells show power conversion efficiency of 11%.